El aprendizaje cooperativo en las clases de e/le: una herramienta pedagógica para el desarrollo de la destreza oral de los alumnos del 2° año de la enseñanza media de la escuela Terezinha de Jesus Ferreira Lima - FONSECA, Larissa Azevedo (2019)
This article is the result of an investigation into the cooperative teaching/learning process for the development of oral skills in Spanish as a foreign language (E/LE). The research was subsigued by a bibliographic study and subsequently a Field survey conducted in the class E/LE of the 2º year students of the Middle School of the Terezinha de Jesus Ferreira Lima, in Abaetetuba/PA, where it was applied. Cooperation activities in order to analyze their impact on the development of the oral expression of these learners. Therefore, this work counted on the contributions of authors such as, David y Roger J. Jonson (1999), Cerdá valles, C., & Querol Julián, M (2014), as well as Piaget (1995) and Vygotsky (1988).